Self-Evaluation of Proficiency Levels by Alumni-Teachers based on Content Knowledge and Pedagogy - Karumathy, Ponelyn (International Journal of Arts, Sciences and Education, 2024)
This study assesses the graduated Harris Memorial College (HMC) students’ ability as early childhood teachers based on the Philippine Professional Standards for Teachers (PPST). The research uses a quantitative and qualitative approach to look into the self-assessments of alumni in the domain of content knowledge and pedagogy. Quantitative findings indicated that all sub-domains under "Content Knowledge and Pedagogy" rated "Very Good," the highest proficiency being in teaching strategies for literacy and numeracy (mean: 4.27) and the lowest in understanding research-based teaching principles (mean: 3.77). The weighted mean of the domain was 4.09, which reflected high proficiency. Qualitative analysis of alumni interviews revealed six recurring themes as follows: appropriate and effective teaching strategies, engaging learners, creative use of resources and technology, adequate preparation, research-based principles, and lesson integration. "Appropriate and Effective Teaching Strategies" was the most frequently mentioned theme and supports the quantitatively found results, while the lower frequencies concerning research-based principles and lesson integration represent areas for future improvement. These results underscore an integration of good content with innovative pedagogies or teaching methods and resonate, therefore, with educational research and biblical teaching principles. Actionable insights based on these findings can offer further refinements for HMC’s teacher education curriculum by enhancing graduates’ competencies in early childhood education.